Dynamics of Simultaneous and Imitative Bodily Coordination in Trust and Distrust - Cornejo, Carlos; Hurtado, Esteban; Cuadros, Zamara; Torres-Araneda, Alejandra; Paredes, Javiera; Olivares, Himmbler; Carré, David; Robledo, Juan P. (Frontiers in Psychology, 2018)
Body synchronization between interacting people involves coordinative movements in time, 5 space and form. The introduction of newer technologies for automated video analysis and motion 6 tracking has considerably improved the accurate measurement of coordination, particularly in 7 temporal and spatial terms. However, the form of interpersonal coordination has been less 8 explored. In the present study we address this gap exploring the effect of trust on temporal and 9 morphological patterns of interpersonal coordination. We adapted an optical motion-capture 10 system to record spontaneous body movements in pairs of individuals engaged in natural 11 conversations. We conducted two experiments in which we manipulated trust through a breach 12 of expectancy (Study 1: 10 trustful and 10 distrustful participants) and friendship (Study 2: 20 13 dyads of friends and 20 dyads of strangers). In Study 1, results show the participants’ strong, 14 early mirror-like coordination in response to the confederates’ breach of trust. In Study 2, imitative 15 coordination tended to be more pronounced in pairs of friends than in pairs of non-friends. Overall, 16 our results show not only that listeners move in reaction to speakers, but also that speakers react 17 to listeners with a chain of dynamic coordination patterns affected by the immediate disposition 18 of, and long-term relationship with, their interlocutors.